Implementation of Wattpad in Understanding Popular Literature as an Effort for Improving Reading Comprehension - Dinar Faiza; Ade Christanty Yudha Bestari (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
This study aimed to examine the implementation of using Wattpad in understanding popular literature as an effort to train reading comprehension for English Education students at UNU Purwokerto. Researchers applied Wattpad as an alternative medium for learning to read popular literature. The research method used descriptive qualitative. Data collection used purposive sampling by taking a sample of 21 students. Data collection techniques used tests, interviews, observation, and documentation. Through this research, several findings were found. First, by using Wattpad, it increases reading comprehension of popular literary works. It is seen from 76% of students having a